2018
DOI: 10.2147/hiv.s166245
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of antiretroviral effect on mitochondrial DNA depletion among HIV-infected patients in Bali

Abstract: BackgroundNucleoside reverse transcriptase inhibitors (NRTIs) are the cornerstone of highly active antiretroviral therapy combination regimens for HIV infection. Unfortunately, NRTIs have been noticeably associated with many adverse effects related to mitochondrial toxicity leading to mitochondrial deoxyribonucleic acid (mtDNA) depletion. However, similar mitochondrial dysfunction has recently been found even in antiretroviral therapy-naïve patients, suggesting HIV itself could contribute to this abnormality. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 30 publications
0
4
0
Order By: Relevance
“…The main reason is that they were unaware of sexually transmitted illnesses and had unprotected intercourse with their clients. 36 Similar like Surabaya, an investigation in North Sulawaesi showed CRF01_AE gene is the major subtype of HIV-1 infection. 30 The major subtypes prevalent in another study in Papua and West Papua provinces are also CRF01_AE and subtype B.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The main reason is that they were unaware of sexually transmitted illnesses and had unprotected intercourse with their clients. 36 Similar like Surabaya, an investigation in North Sulawaesi showed CRF01_AE gene is the major subtype of HIV-1 infection. 30 The major subtypes prevalent in another study in Papua and West Papua provinces are also CRF01_AE and subtype B.…”
Section: Discussionmentioning
confidence: 88%
“…39 Another evaluation of ARV effect in Bali reported that the patients who undergo more than12 months of NRTIs treatment show a decrease in the mtDNA:nDNA ratios. 36 Study in Surabaya showed that transmitted drug resistance of RT inhibitors was detected in 4.3% of the samples. 3 A study in Papua showed high prevalence of HIV-1 patient because health behavior that associated with social culture.…”
Section: Discussionmentioning
confidence: 99%
“…11,20 However, other studies found greater loss of mtDNA content over time with long-term treatment in HIVinfected children 4 and adults. 21,22 There are a number of possible explanations for mitochondrial impairment in our study sample of HIV-infected children with prolonged viral control who were initiated on ART early in life. Despite suppression of plasma VL to low concentrations, viral reservoirs 23 and viral associated proteins may persist, 24,25 thereby impairing mitochondrial function.…”
Section: Discussionmentioning
confidence: 99%
“…The Cognitive Adaptive Test/Clinical Linguistic and Auditory Milestone Scale (CAT/CLAMS) was designed for use by primary pediatric health-care providers to screen children for cognitive delay using minimal equipment in a shorter time (usually 15-20 min) [4]. CAT/CLAMS has been demonstrated https://www.id-press.eu/mjms/index in normal children as well as high-risk groups of developmental delayed children between 1 and 36 months of age [7], [8]. This study aimed to assess the correlation of Capute score with CD4 count among HIVinfected children in Sanglah Hospital, Bali, Indonesia.…”
Section: Introductionmentioning
confidence: 99%